Optic glioma and precocious puberty in a girl with neurofibromatosis type 1 carrying an R681X mutation of NF1: case report and review of the literature - Mirjana Kocova; Elena Kochova; Elena Sukarova-Angelovska (BMC Part of Springer Nature, 2015)
Neurofibromatosis type 1 (NF1) is a common autosomal dominant genetic disorder with an extremely variable phenotype. In childhood NF1 can be associated with optic glioma and central precocious puberty; the latter is more common when the optic chiasm is affected. The mutational spectrum of the NF1 gene is wide and complex; R681X is a rare severe mutation of the NF1 gene known to cause truncation of neurofibromin, with only ten reported cases in the literature so far.